Farmland tenure in China: Comparing legal, actual and perceived security. (January 2015) - Ma, Xianlei; Heerink, Nico; Feng, Shuyi; Shi, Xiaoping
Highlights: We examine the magnitudes and causes of legal, actual and perceived land tenure (in)security in rural China. Two farm household surveys conducted in Gansu province and Jiangxi province are used as case studies. Households experience high legal security, but substantial insecurity of actual and perceived land tenure. Social security considerations, ambiguous laws and self-governance rules contribute to perceptions of tenure insecurity. Tenure security is higher in the Gansu case due to land quality improving investments made in that region. Abstract: This paper examines the magnitudes of legal security, actual security and perceived security of farmland tenure, and the causes of currently prevailing land tenure insecurity in rural China. Two farm household surveys conducted in the northwest of Gansu province in 2010 and in the northeast of Jiangxi province in 2011 are used as case studies. Although recent land tenure reforms have significantly improved legal tenure security, we find that farm households still experience substantial insecurity of actual and perceived land tenure. We argue that social security considerations, ambiguous formulations of laws, and village self-governance rules are three important underlying causes. Actual and perceived land tenure security is lowest in the case study region in Jiangxi province even though the share of off-farm income in rural household incomes is much larger in that region. We explain this finding from investments in land quality improvement made by rural households in the Gansu case study region, the larger per capita land resources in that region, and the limited social security provided by off-farm employment.